Does an effective board of directors have any impact on audit report lag? - Hashim, Ummi Junaidda; Abdul Rahman, Rashidah (2011)
This siud ' examines the linI between corporate governance mechanisms and audii i-eport lag among 2i$ 8 c omponres li.clef or Burta Malaysia for a three-yeor period from 2HH7 io 20H9. Four characteristics of boai-d oJ’ dit-ectors rire examined (board independence, board diligence, board expertise and CEG dualii i') on iheir e(ectiveness in assuring ihe timeliness of audit reports. The results show that audit report fag /dr the listed companies in Malnysio Fonges from 36 doys to 184 days for ihe three year period and ihere are significant negative relationships between board diligence and uudit report lag. Tliiy .study found iliat the number of nteeting.s held by fhe board n/ directors in a company is able to reduce audit report lag. indicates he board is discharging their role towards the company. This study, howether, could not provide any evidence concerning the link between hoard independence. board expertise ond CEO duality on oudit report lag.